The European Union in a Changing World Order
XIII, 280 p. 9 illus.
Keywords: This book explores how the European Union responds to the ongoing challenges to the liberal international order. These challenges arise both within the EU itself and beyond its borders, and put into question the values of free trade and liberal democracy. The book’s interdisciplinary approach brings together scholars from economics, law, and political science to provide a comprehensive analysis of how shifts in the international order affect the global position of the EU in dimensions such as foreign and security policy, trade, migration, populism, rule of law, and climate change. All chapters include policy recommendations which make the book particularly useful for decision makers and policy advisors, besides researchers and students, as well as for anyone interested in the future of the EU. Antonina Bakardjieva Engelbrekt is Professor of European Law at Stockholm University, Sweden, and Chair of the Swedish Network for European Legal Studies. Niklas Bremberg is Associate Professor of Political Science at Stockholm University, Sweden, and Senior Research Fellow at the Swedish Institute of International Affairs. Anna Michalski is Associate Professor of Political Science at Uppsala University, Sweden, and Chair of the Swedish Network for European Studies in Political Science. Lars Oxelheim is Professor at University of Agder, Norway, and affiliated with the Research Institute of Industrial Economics, Stockholm and Lund University, Sweden. He is founder of the Swedish Network for European Studies in Economics and Business.